Deformation prediction analysis of sandstone coal mine goaf based on discrete element method and probability integration method - Ruonan, Gao; Xi, Chen; Yuchen, Wang; Gen, Liu; Jin, Li (Frontiers in Materials, 2026)
Accurate prediction of goaf settlement is essential for evaluating surface movement and deformation and for understanding overburden failure mechanisms in sandstone coal mine goafs. Coal seam extraction commonly induces significant overburden failure, stress redistribution, surface settlement, and ground fissures, which pose threats to mining safety and ecological stability, particularly under conditions of thick loose strata and thin bedrock. In this study, a sandstone coal mine in Ningxia, China, is selected as the research site. A three-dimensional discrete element model is established using 3DEC to simulate overburden deformation during coal seam extraction under complex geological conditions. The evolution of plastic zones, displacement fields, stress distribution, and surface settlement at different mining stages is systematically analyzed. Meanwhile, the probability integration method is employed to conduct dynamic prediction of surface settlement, with key parameters determined through inversion of field monitoring data. The results indicate that coal seam mining results in an elliptical settlement basin, with a maximum surface settlement of 3.77 m occurring at the goaf center. Shear failure is dominant along coal pillar edges, while significant stress concentration develops in the central goaf area. The settlement predictions obtained from the probability integration method show strong agreement with numerical simulation results, with prediction errors controlled within 3.6%–6.0%. These findings demonstrate that the combined application of discrete element numerical simulation and the probability integration method is effective for predicting surface settlement and analyzing overburden failure mechanisms under thick loose strata and thin bedrock conditions. The study provides a robust theoretical basis and practical reference for surface stability evaluation, hazard prevention, and ecological restoration in coal mining areas.